DA Based Systematic Approach Using Speculative Addition for High Speed DSP Applications - Reddy Hemantha, G; Varadarajan, S; N. Giriprasad, M (International Journal of Engineering and Technology, 2018)
In recent years Parallel-prefix topologies has been emerged to offer a high-speed solution for many DSP applications. Here in this paper carrier approximation is introduced to incorporate speculation in Han Carlson prefix method.Â  And overall latency is considerably reduced using single Brent-Kung addition as a pre and post processing unit. In order to improve the reliability error detection network is combined with the approximated adder and it is assert the error correction unit whenever speculation fails during carries propagation from LSB segment to MSB unit. The proposed speculative adder based on Han-Carlson parallel-prefix topology attains better latency reduction than variable latency Kogge-Stone topology. Finally, multiplier-accumulation unit (MAC) is designed using serial shift-based accumulation where the proposed speculative adder is used for partial product addition iteratively. The performance merits and latency reduction of proposed adder unit is proved through FPGA hardware synthesis. Obtained results show that proposed MAC unit outperforms both previously proposed speculative architectures and all other high-speed multiplication methods.Â Â